2018
DOI: 10.3892/mco.2018.1769
|View full text |Cite
|
Sign up to set email alerts
|

The Elental� elemental diet for chemoradiotherapy‑induced oral mucositis: A prospective study in patients with oral squamous cell carcinoma

Abstract: Oral mucositis is a common adverse effect of cancer treatment that can increase the risk for local and systemic infection. This prospective study was designed to evaluate the preventive effects of an amino-acid-rich elemental diet (ED), Elental ® , on radiotherapy-or chemoradiotherapy-induced mucositis in oral squamous cell carcinoma (OSCC) patients. Fifty patients were enrolled in this prospective study, who had received radiation (60-70 Gy) with/without chemotherapy [S-1, UFT, cisplatin (CDDP), docetaxel (DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…Further details about the literature search process are provided in Figure 1. Relevant studies were identified [52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68], and their results are summarized in Table 2 and Table 3.…”
Section: Review On the Use Of Oligomeric Enteral Nutrition Formulamentioning
confidence: 99%
See 4 more Smart Citations
“…Further details about the literature search process are provided in Figure 1. Relevant studies were identified [52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68], and their results are summarized in Table 2 and Table 3.…”
Section: Review On the Use Of Oligomeric Enteral Nutrition Formulamentioning
confidence: 99%
“…Regarding chemotherapy-induced intestinal mucositis [60,61,62,63,64,65,66,67,68] (Table 3), all the studies we have found used the same oligomeric formula of enteral nutrition (Elental ® ). In total there are 345 patients, of whom 203 were treated with this oligomeric enteral nutrition, and the rest are controls without enteral nutrition.…”
Section: Review On the Use Of Oligomeric Enteral Nutrition Formulamentioning
confidence: 99%
See 3 more Smart Citations